2012
DOI: 10.1186/1546-0096-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and color Doppler in juvenile idiopathic arthritis: diagnosis and follow-up of ultrasound-guided steroid injection in the wrist region. A descriptive interventional study

Abstract: BackgroundThe wrist region is one of the most complex joints of the human body. It is prone to deformity and functional impairment in juvenile idiopathic arthritis (JIA), and is difficult to examine clinically. The aim of this study was to evaluate the role of ultrasonography (US) with Doppler in diagnosis of synovitis, guidance of steroid injections, and follow-up examinations of the wrist in JIA.MethodsIn 11 patients (median age 12.5 years, range 2-16), 15 wrists with clinically active arthritis were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…In our present study, Doppler flow was detected in 86% of the 22 diseased areas with synovial hypertrophy on US. Those observations are comparable to our previous findings, using the same definitions of synovial hyperemia, the same US equipment and Doppler settings, in the ankle (89%, [18]) and wrist (88%) regions [19]. Other studies in JIA patients have shown hyperemia in 93% of symptomatic MCP joints [20] and 77% of symptomatic knees [21].…”
Section: Discussionsupporting
confidence: 89%
“…In our present study, Doppler flow was detected in 86% of the 22 diseased areas with synovial hypertrophy on US. Those observations are comparable to our previous findings, using the same definitions of synovial hyperemia, the same US equipment and Doppler settings, in the ankle (89%, [18]) and wrist (88%) regions [19]. Other studies in JIA patients have shown hyperemia in 93% of symptomatic MCP joints [20] and 77% of symptomatic knees [21].…”
Section: Discussionsupporting
confidence: 89%
“…On follow-up, ultrasound can demonstrate normalization or regression of hyperaemia and synovial hypertrophy. 20,51 Similar findings have been shown when ultrasound is used to follow up disease response to antirheumatic drugs 52 and biologic therapies 53 in adults.…”
Section: Disease Activity Assessment and Comparison With Clinical Asssupporting
confidence: 55%
“…MSUS in monitoring the disease activity and response to treatment MSUS imaging can also play a key role in guiding steroid injections into joints, tendon sheathsand even tendon insertions (entheses) [46][47][48]. Local corticosteroid (preferably triamcinolone hexacetonide) injections are a common treatment for young patients with JIA, well tolerated and effective for several months, used particularly in the oligoarthritis subset of JIA.…”
Section: Pathological Us Findings In Patients With Different Rheumatomentioning
confidence: 99%
“…They can also be used when systemic anti-inflammatory treatment fails to control isolated arthritis or tenosynovitis. The benefits and safety of MSUS with PD as guidance of steroid injections has been demonstrated in the symptomatic wrist and ankle regions of JIA patients by Laurell et al [46,47]. Using US guidance allows full needle visualization in real-time, including the needle tip.…”
Section: Pathological Us Findings In Patients With Different Rheumatomentioning
confidence: 99%